Plusvalía semántica: bosquejo de una teoría pragmática de la recepción de los medios - Klaus Bruhn Jensen (Estudios sobre las Culturas Contemporáneas)
Taking from critical theory the concepts of economic and repressive surplus, the term meaning surplus is presented in order to characterise reception of massive communication. This article exemplifies the impact of meaning production by different social classes, with special reference to the audience. While recent analyses of reception have emphasised the active and autonomous nature of the audience as producer of meaning, it is here argued that there are important social structures that shape reception beforehand. The social aspects of meaning can be better anEilysed within a pragmatic theory of communication.